Managing the cyber-physical security for unmanned aerial vehicles used in perimeter surveillance - Al-Bkree, Mahmod (International Journal of Innovative Research and Scientific Studies, 2023)
This paper discusses the vulnerabilities of perimeter surveillance unmanned aerial vehicles to cyber-physical security threats and discusses some approaches to manage them, as most cyber threats to the UAVs coming through their onboard wireless transceiver, we are suggesting an Antennas propagation type that limit the vector of the threat, also the importance of vulnerabilities scanner to evaluate the system risks. And addressing the limited energy and computation power resources onboard, a computation efficient onboard encryption method is proposed, and a sign cutting machine vision algorithm to provide warning of suspicious activity detected on interrupted surveillance imagery. The focus of this analysis is to manage the vulnerabilities of the system during both its operation time and its standby time, this is done by performing a checklist of computerized tests periodically and comparing two or more results to discover any unexpected changes. We showed that the onboard resources can be utilized more efficiently securing itself and the system from possible intrusion, however, some heavy calculation tasks still need to be performed on the ground control station which is causing some latency problem to such time sensitive operation. We have demonstrated that image registration techniques have produced useful results when applied to analyze the differences between two scene images.